The - Bly, Robert W. (Thomson,American Marketing Association, 2006)
Discover how white papers can create interest, generate leads, build relationships and drive sales. THE WHITE PAPER MARKETING HANDBOOK is the first of its kind, and offers the inside information from top companies on how to create effective white papers using a variety of media. Practical and loaded with illustrations from industry giants like IBM and Home Depot, THE WHITE PAPER MARKETING HANDBOOK also shows you how white papers fit into successful Integrated Marketing Communications efforts. Get on the cutting-edge of marketing using white papers with THE WHITE PAPER MARKETING HANDBOOK